Home automation system with arduino wireless sensor network - Azizul, Lau (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Home automation is the control of any or all electrical devices in our home, whether we are there or away. Home automation is one of the most exciting developments in technology for the home that has come along in decades. There are hundreds of products available today that allow us control over the devices automatically, either by remote control, smartphones or even by voice command. Nowadays, traditional home system requires human working force to operate. Which mean it still need human intervention to turn certain home appliances like lighting, air conditioning, fan and other. In term of performing tasks, human physical performance is slow compared to the automation system. In addition when we used human force there are possibility error or accident may occur due to our awareness and reaction. For disabled peoples, is hard for them to operate the home appliances without human or tools assist. Certain home appliances is also dangerous for them and need more careful behaviour while using it, plus with wet hands. Moreover, the traditional home system also consumes more electrical energy, when remain unattended for couple of hours. The Home Automation System with Arduino Wireless Sensor Network is focus on improving living home standard where the user can control their home lighting and home appliance with their smartphones and also using their Personal Computer (PC). User can turn on or off their home appliance using their PC. This system is link with each other by using WiFi router. We use Arduino platform hardware especially for the microcontroller and WiFi Shield. We also used contactless temperature sensor to measure human body temperature and Pyroelectric Infrared Sensor to detect motion. In addition, this system integrated with Cloud server to perform notification where a notification email will be sent to the user which can be view in smartphone or PC .